Performance enhancement of double pass photovoltaic/thermal solar collector using asymmetric compound parabolic concentrator (PV/T-ACPC) for façade application in different climates. (June 2022) - Wan Roshdan, Wan Nur Adilah; Jarimi, Hasila; Al-Waeli, Ali H.A.; Ramadan, Omar; Sopian, Kamaruzzaman
Abstract: Symmetrical compound parabolic concentrators (CPC) for a stationary double pass photovoltaic thermal (PV/T) air solar collector has been widely employed. However, for high yearly energy delivery, the solar incidence angle must be within the full acceptance angle of the CPC which is a challenge to determine for a symmetrical CPC. This paper presents the performance enhancement of a double pass photovoltaic/thermal air solar collector using an asymmetric compound parabolic concentrator (PV/T-ACPC) suitable for building façade application. Mathematical modelling was developed and validated against established experimental results. The potential of double pass PV/T-ACPC was then evaluated for different locations that represent low, mid, and high latitudes. Double pass PV/T-ACPC outperforms the conventional symmetric compound parabolic concentrator (PV/T-CPC) and the conventional flat type of double pass PV/T solar air collector. When compared with conventional flat type, the average percentage increase in the average daily total power yield for the PV/T-ACPC is as high as 14% and 50% for the low and mid-latitude, and high latitude countries, respectively. Meanwhile, for the PV/T CPC, the percentage of the average daily total power yield was slightly negative in value for low and mid-latitude countries, which indicates worse performance compared to the conventional type.